Focus on leadership servant-leadership for the twenty-first century - Spears, Larry C. (New York J. Wiley & Sons, 2002)
This collection of inspiring essays focuses on the practice of servant-leadership in organizational and business settings. Focus on Leadership addresses how servant-leadership is now increasingly recognized as being on the forefront of emerging leadership thinking
Includes bibliographical references
Keywords: Leadership